2008
DOI: 10.1105/tpc.107.053249
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Flavonol Glycosylation Profile in the Arabidopsis rol1 Mutants Results in Alterations in Plant Growth and Cell Shape Formation

Abstract: Flavonoids are secondary metabolites known to modulate plant growth and development. A primary function of flavonols, a subgroup of flavonoids, is thought to be the modification of auxin fluxes in the plant. Flavonols in the cell are glycosylated, and the repressor of lrx1 (rol1) mutants of Arabidopsis thaliana, affected in rhamnose biosynthesis, have a modified flavonol glycosylation profile. A detailed analysis of the rol1-2 allele revealed hyponastic growth, aberrant pavement cell and stomatal morphology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 57 publications
7
160
0
Order By: Relevance
“…In fact, major six flavonol contents in flowers are ;10-to 70-fold higher than in leaves (YonekuraSakakibara et al, 2007). The role of RHM1 for UDP-rhamnose supply to flavonols was also supported by a recent report with young shoots of the rol1 mutants (Ringli et al, 2008) and our data with RHM1 knockdown mutants (SALK_027926 and SALK_143589; see Supplemental Figure 4 online).…”
Section: Rhm1 Is Involved In Flavonol Biosynthesissupporting
confidence: 73%
“…In fact, major six flavonol contents in flowers are ;10-to 70-fold higher than in leaves (YonekuraSakakibara et al, 2007). The role of RHM1 for UDP-rhamnose supply to flavonols was also supported by a recent report with young shoots of the rol1 mutants (Ringli et al, 2008) and our data with RHM1 knockdown mutants (SALK_027926 and SALK_143589; see Supplemental Figure 4 online).…”
Section: Rhm1 Is Involved In Flavonol Biosynthesissupporting
confidence: 73%
“…The rol1-2 mutant was identified in a screen for alterations in cell wall structures and shows modifications in the Rha-rich cell wall component pectin (43). In addition, rol1-2 also shows changes in the flavonol glycosylation profile, mainly a reduction in the degree of rhamnosylation, whereas the overall quantity of flavonols is not affected (30,44). This confirms the importance of RHM1, which is coexpressed with genes important for flavonol biosynthesis (26) and for flavonol glycosylation.…”
supporting
confidence: 51%
“…In vitro experiments show activity of flavonol aglycones, suggesting that these are the compounds active in modulating polar auxin transport (10,17,18,20). However, the identification of mutant phenotypes induced by changes in the flavonol glycosylation profile suggests function for at least some flavonol glycosides (30,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, preliminary analyses of acropetal transport with the alleles described here showed that the tt4-2 and tt7-2 phenotypes are not equivalent, with tt7-2 showing an intermediate phenotype between the wild type and tt4-2 (data not shown). Furthermore, kaempferol and its derivatives have been shown to have distinct developmental roles in leaves based on analysis of the rol1-3 mutant, which is defective in Rha biosynthesis and flavonoid glycosylation (Ringli et al, 2008). This suggests that, in other tissues and auxin transport streams, kaempferol and its derivatives may have a distinct function.…”
Section: Discussionmentioning
confidence: 99%